2018
DOI: 10.1186/s13287-018-0938-6
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell therapy for diabetic foot ulcers: a review of preclinical and clinical research

Abstract: BackgroundDiabetic foot ulcer (DFU) is a severe complication of diabetes, preceding most diabetes-related amputations. DFUs require over US$9 billion for yearly treatment and are now a global public health issue. DFU occurs in the setting of ischemia, infection, neuropathy, and metabolic disorders that result in poor wound healing and poor treatment options. Recently, stem cell therapy has emerged as a new interventional strategy to treat DFU and appears to be safe and effective in both preclinical and clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
131
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(147 citation statements)
references
References 102 publications
0
131
0
2
Order By: Relevance
“…The introduction of cell therapy has made dramatic contribution to science and continue to expand in value and utility in regenerative medicine and disease therapeutics. Experimental and clinical applications of cell therapy has covered many diseases including cardiovascular conditions [1][2][3], Parkinson's disease [4,5], osteoarthritis [6], diabetes [7,8], neurological conditions [9], wounds [10], malignancies [11], among others. The special characteristic properties of MSCs have been exploited in countless research field with fascinating outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of cell therapy has made dramatic contribution to science and continue to expand in value and utility in regenerative medicine and disease therapeutics. Experimental and clinical applications of cell therapy has covered many diseases including cardiovascular conditions [1][2][3], Parkinson's disease [4,5], osteoarthritis [6], diabetes [7,8], neurological conditions [9], wounds [10], malignancies [11], among others. The special characteristic properties of MSCs have been exploited in countless research field with fascinating outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has demonstrated that, compared with exogenous EpSCs, resident EpSCs are more important in tissue remodeling and wound closure; the loss of resident EpSCs, impairment of their migration capacity, and/or excessive differentiation may lead to delay in wound healing. Accordingly, stem cell-based therapy is gaining recognition as a way to improve healing outcomes [6].…”
Section: Introductionmentioning
confidence: 99%
“…This results in poor wound healing and poor treatment options. In a review article, Lopes et al have stated that existing proof points toward stem cell therapy as a persuasive cure for DFU 32 . Clinical and preclinical research studies have not provided any consensus regarding the optimum category of stem cell that should be used and there is no well-known optimal route or regimen for delivery of the stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Differences within preclinical study designs suggest the need for an agreement regarding an optimum animal model that suggests translation to human studies. Variations in the stem cell category and source, route, and regimen for administration also confound easy interpretation and generalization of the results 32 . According to Lopes et al, there is an urgent need for additional experimentation to find a good animal model and persuasive regimens of stem cell therapy for treating severe cases of DFU.…”
Section: Discussionmentioning
confidence: 99%